Fables of modernity : literature and culture in the English eighteenth century - Brown, Laura, 1949- (Cornell University Press, 2001)
Fables of Modernity expands the territory for cultural and literary criticism by introducing the concept of the cultural fable. Laura Brown shows how cultural fables arise from material practices in eighteenth-century England. These fables, the author says, reveal the eighteenth-century origins of modernity and its connection with two related paradigms of difference-the woman and the "native" or non-European. The collective narratives that Brown finds in the print culture of the period engage such prominent phenomena as the city sewer, trade and shipping, the stock market, the commercial printing industry, the "native" visitor to London, and the household pet. In connecting imagination and history through the category of the cultural fable, Brown illuminates the nature of modern experience in the growing metropolitan centers, the national consequences of global expansion, the volatility of credit, the transforming effects of capital, and the domestic consequences of colonialism and slavery